Precision genome editing in plants using gene targeting and prime editing: existing and emerging strategies. Issue 10 (11th July 2022) - Hassan, Md Mahmudul; Yuan, Guoliang; Liu, Yang; Alam, Mobashwer; Eckert, Carrie A.; Tuskan, Gerald A.; Golz, John F.; Yang, Xiaohan
Abstract: Precise modification of plant genomes, such as seamless insertion, deletion, or replacement of DNA sequences at a predefined site, is a challenging task. Gene targeting (GT) and prime editing are currently the best approaches for this purpose. However, these techniques are inefficient in plants, which limits their applications for crop breeding programs. Recently, substantial developments have been made to improve the efficiency of these techniques in plants. Several strategies, such as RNA donor templating, chemically modified donor DNA template, and tandem‐repeat homology‐directed repair, are aimed at improving GT. Additionally, improved prime editing gRNA design, use of engineered reverse transcriptase enzymes, and splitting prime editing components have improved the efficacy of prime editing in plants. These emerging strategies and existing technologies are reviewed along with various perspectives on their future improvement and the development of robust precision genome editing technologies for plants. Graphical Abstract and Lay Summary: Gene targeting (GT) and prime editing are currently the best approaches for precise editing of plant genomes. These techniques are, however, inefficient in plants, limiting their applications in genetic improvement of crops. Recent developments based on the use of positive–negative selection, RNA donor templating, chemically modified donors, and viral vectors have improved the efficacy of GT in plants. On the other hand, pegRNA engineering, development of new prime editors, use of alternative and engineered Cas proteins, and reverse transcription (RT) enzymes have improved the efficacy of prime editing. These strategies, along with their future improvement, are discussed in this review.